Comparative analyses and phylogenetic dependence in traits and trends of the Dipterocarpaceae - Malik, Nazrin; Edwards, David; Freckleton, Robert P. (John Wiley and Sons, 2025)
The role of trait evolution in shaping the functional and ecological diversity of tropical forests remains poorly understood. Analyses of trait variation as a function of evolutionary history and environmental variables should reveal the drivers of species distributions, as well as generate insights valuable to conservation. Here, we focus on the Dipterocarpaceae, the key plant family underpinning the hyperdiversity of South-East Asian tropical forest canopies and of major conservation concern due to over-exploitation for timber, cultivation, and climate change. Our objectives are to (i) assess whether dipterocarp species traits are phylogenetically conserved through a phylogenetic signal, indicating phylogenetic niche conservatism (PNC); (ii) determine the drivers of dipterocarp species distribution; (iii) examine the relationship between morphological traits with habitat factors; and (iv) assess the correlation between conservation status and phylogeny. We compiled a dataset of species-level plant traits of the Dipterocarpaceae together with population-level ecological trends. We found substantial evidence of phylogenetic conservatism of plant traits in dipterocarp species, with a moderate to strong phylogenetic signal, and that the elevational gradient shapes dipterocarp species distribution pan-tropically. Morphological traits including height and diameter show phylogenetically dependent relationships with soil type, while shade tolerance traits are related to survival. We find that conservation status is related to phylogeny and correlated with population trend status, suggesting that decreasing population trends correlated with conservation status. Overall, our analyses show that functional traits and ecological trends of dipterocarp species are shaped by the phylogenetic history. Our study highlights that conservation strategies require consideration of the consequences of these relationships for long-term population changes.